The influence of fuel oil prices on profitability with corporate social responsibility as moderating variable (Empirical study of companies in oil and gas mining industry listed on Indonesia Stock Exchange) - Fitriaty, Fitriaty; Lubis, Tona Aurora; Trilianah, Ningsi (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2018)
This study aims to analyze the effect of fuel prices on profitability with Corporate Social Responsibility (CSR) as a moderating variable in the mining industry companies listed in Indonesia Stock Exchange 2013-2016 period. This study uses Partial Least Square (PLS), which aims to predict the relationship between variables. Measurement model used validity and reliability, while the structural model used to test causality. The results of this study indicate that the price of fuel oil has no significant effect on the profitability of the company. Corporate Social Responsibility (CSR) as a moderating variable can affect the relationship of the price of fuel on profitability.